176k views
2 votes
PLEASE HURRRRRY!

solve the system of equations by elimination!
x - 5y =1
2x + 5y = 17

User Wayan
by
5.5k points

2 Answers

5 votes

Answer:

(6, 1).

Explanation:

x - 5y =1

2x + 5y = 17 Adding the 2 equations eliminates the term in y:

3x + 0 = 18

x = 6.

Plug x = 6 into the first equation:

6 - 5y = 1

-5y = -5

y = 1.

User JNM
by
6.2k points
4 votes

Answer:

(6 , 1)

Explanation:

x - 5y =1 (1)

2x + 5y = 17 (2)

(1) + (2) ⇒ 3x = 1 + 17

⇒ 3x = 18

⇒ x = 6

now, we just replace x by 6 in equation (1) ⇒ 6 - 5y =1 ⇒ y = 1

User Storm Surge
by
5.7k points